DYNAMICS OF CONSUMER BEHAVIOR AMONG PIPS UIN JAKARTA STUDENTS IN THE DIGITAL AGE - Nurjanah, Jihan; Andriliyani, Farhah; Furqon, Aqimul; Ramda, Rimaysa; Saefudin, Arif (Yayasan Amanah Nur Aman, 2025)
This study aims to analyze the dynamics of consumptive behavior among students of the Social Sciences Education Study Program (PIPS) at UIN Jakarta in the digital era. The development of digital technology and social media has changed students' consumption patterns from those originally driven by rational needs to behaviors influenced by emotions and the search for social identity. This study uses a qualitative approach with a case study design, involving 3 active students selected purposively. Data were collected through in-depth interviews, participant observation, and documentation. The results show that most students prefer online shopping because of its ease of access, product variety, and numerous attractive promotions. Social media such as TikTok, Instagram, and Shopee Live play an important role in shaping purchasing interests through digital promotions and the influence of influencers. Psychological factors such as Fear of Missing Out (FOMO) and social pressure from peers also contribute to the emergence of impulsive consumptive behavior. However, some students are beginning to show financial awareness by trying to distinguish between needs and wants and managing their finances more wisely. This study concludes that the consumptive behavior of PIPS UIN Jakarta students in the digital era is a form of adaptation to the influence of technology and digital culture, but it can be controlled through the strengthening of financial literacy. Therefore, universities need to play an active role in instilling digital financial literacy to shape smart, critical, and sustainable consumptive behavior.